Association of country-specific socioeconomic factors with survival of patients who experience severe classic acute graft-vs.-host disease after allogeneic hematopoietic cell transplantation: an analysis from the transplant complications working party of the EBMT - Frankiewicz, Andrzej; Peczynski, Christophe; Giebel, Sebastian; Harrington, Alenca; Socié, Gerard; Niederwieser, Dietger; Scheid, Christoph; Bornhäuser, Martin; Kröger, Nicolaus; Elmaagacli, Ahmet; Afanasyev, Boris; Dreger, Peter; et al. (Frontiers in immunology, 2020)
Acute graft-versus-host disease (aGvHD) is one of the most frequent causes of transplant-related mortality (TRM) after allogeneic hematopoietic cell transplantation (alloHCT). Its treatment is complex and costly. The aim of this study was to retrospectively analyze the impact of country-specific socioeconomic factors on outcome of patients who experience severe aGvHD. Adults with hematological malignancies receiving alloHCT from either HLA-matched siblings (n=1328) or unrelated donors (n=2824) developing grade 3 or 4 aGvHD were included. In univariate analysis, the probability of TRM at 2 years was increased for countries with lower current Health Care Expenditure (HCE, p=0.04), lower HCE as % of Gross Domestic Product per capita (p=0.003) and lower values of the Human Development Index (p=0.02). In a multivariate model, the risk of TRM was most strongly predicted by current HCE (HR=0.76, p=0.006). HCE >median was also associated with reduced risk of the overall mortality (HR 0.73, p=0.0006) and reduced risk of treatment failure (either relapse or TRM; HR 0.77, p=0.004). We conclude that country-specific socioeconomic factors, in particular current HCE, are strongly associated with survival of patients who experience severe aGvHD.
Gesehen am 23.09.2020